The role of psychological resilience and aggression in injury prevention among martial arts athletes - Patenteu, Ionuț; Gawrych, Roman; Bratu, Mircea; Vasile, Luciela; Makarowski, Ryszard; Bitang, Andrei; Nica, Sarah Adriana (Frontiers in Psychology, 2024)
Introduction For martial artists, the ability to manage reactions in the face of adversity and bounce back after a stressful event can have major impact on performance. The scope of the research is to investigate martial artists’ level of resilience and aggression (Go-ahead, Foul play, and Assertiveness factors), what is specific to athletes and who have suffered from moderate and/or severe injuries (in terms of resilience and three factors of aggression examined), and test the possibility that a psychological variable under investigation can predict athletes’ injury severity. Materials and methods A total sample of 154 athletes from striking combat sports—SC (karate, taekwondo, kickboxing, and boxing), grappling combat sports—GC (judo and BJJ), and mixed martial artists (MMA) participated in the research. For assessing resilience, the Romanian adaptation of the Brief Resilience Scale (BRS) was used, and for aggression, the Romanian adaptation of Makarowski’s Sports Aggression Questionnaire was used. An injury report form was also created and applied to athletes. Results The post-hoc tests (after running a single-factor multivariate analysis of variance) revealed significant differences for resilience and Foul (violent) play between the sports disciplines analyzed. A significant positive correlation was found between athletes’ injury severity and assertiveness in SC and between injury severity and resilience in GC. Through the t-test for independent samples, it was highlighted that the average value for Foul (violent) play is significantly higher in athletes who have suffered mild, moderate, and/or severe injuries compared with martial arts athletes who have suffered from only mild/minor injuries. A binomial logistic regression was also performed to verify to what extent Foul play predicts athletes’ injury severity. Conclusion A low level of Foul (violent) play is linked with a decreased likelihood of moderate and/or severe injuries in martial arts athletes. The study findings suggest that resilience, foul play, and assertiveness have an important role in injury prevention among martial artists.